The first flush analysis of stormwater runoff in a humid climate - Mastouri, Reza; Pourfallah Koushali, Hassan; Khaledian, Mohammad Reza (Journal of Environmental Engineering and Landscape Management, 2023)
This study focuses on the pollutants from urban runoff to Zarjoob River, which is one of the rivers leading to Anzali International Wetland, which was listed in the Montreux Record in 1993 as a site in need of priority conservation. Storm water runoff from a residential area in Rasht (the largest city on Iran’s Caspian Sea coast) was monitored in this study during thirteen rainfall events, with a total of 58 storm runoff samples collected from 2018 to 2019. In most rainfall events, the mean concentration of total suspended solids (TSS) and chemical oxygen demand (COD) were higher than the other pollutants. The event mean concentrations (EMC) of TSS loads ranged from 57.3 mg/L to 682.5 mg/L and from 46.7 mg/L to 590.4 mg/L for COD. The site mean concentrations (SMC) for TSS, COD, total phosphorus (Total P), nitrate-nitrogen (NO3-N), and total lead (Pb) were 219, 205, 1.91, 20.63, and 0.25 mg/L, respectively. The first flush coefficient (b) was used to evaluate the first flushing of various events. The results of the study confirmed that the first flush occurred in all events, and the average ranking of first flush strength among the pollutants was COD > NO3-N > TP > Pb > TSS. Controlling one-third of the initial runoff volume appeared to be critical for managing the quality of urban rivers in humid regions. The findings of this study can be applied to urban runoff management strategies in cities with similar climatic conditions.